Intraguild Interactions Drive the Dynamics of a Complex Community of Globally Invasive Ant Species - Maximillian P. T. G. Tercel; William O. C. Symondson; Jordan P. Cuff; Nik C. Cole; Martine Goder; Kevin Ruhomaun; Vikash Tatayah; Ian P. Vaughan (Molecular Ecology, 2026)
Invasive species adversely affect biodiversity, but little is known about how ecologically similar invaders interact. Such intraguild interactions may drive non‐native community dynamics and their broader impacts on biodiversity. In native systems, intraguild interactions are widespread strong eco‐evolutionary pressures; understanding whether similar patterns occur among invaders is key to predicting invasion outcomes. We investigated the role of intraguild predation in a community of non‐native ant species inhabiting a tropical island with no native ants. Using dietary metabarcoding, we quantified intraguild predation, applied null models to test dietary and spatial preferences, conducted food bait experiments to assess competition for resources, and quantified potential competition strength using a hypergraph network approach. Metabarcoding 755 ants across 12 species revealed that ~50% of prey detections represented ant‐ant consumption. Ants preferentially consumed other ants over native arthropods but only once the globally invasive big‐headed ant, Pheidole megacephala , was removed from the null model analysis due to its hyperabundance. Additionally, 35% of food resources were identified as foci for potential interspecific exploitation where ant species spatially co‐occurred. Pheidole megacephala occupied a key structural role in the community: it frequently competed with others for prey, was consumed less often than expected given its abundance, and was spatially avoided by other ants. Overall, interference competition was dominated by P. megacephala , but exploitation competition was high across the community. These findings suggest that intraguild interactions strongly structure invaded communities, influencing the ecological impact of multiple invaders within the same guild.

Threatened endemic arthropods and vertebrates partition their diets with non‐native ants in an isolated island ecosystem - Maximillian P. T. G. Tercel; Jordan P. Cuff; William O. C. Symondson; Rosemary J. Moorhouse‐Gann; Tom Rhys Bishop; Nik C. Cole; Eric Jolin; Bethan Govier; Johannes Chambon; Rouben Mootoocurpen; Martine Goder; Ian P. Vaughan (Ecology, 2025)
The success of non‐native species depends on their ability to find food, which may ultimately lead to competition with native species and contribute to biodiversity loss in invaded ecosystems. Understanding which food resources are consumed is therefore crucial for evaluating how non‐native species mechanistically fit into native biological communities. Non‐native species may be predators or competitors of native species or may be consumed by native species as a novel source of nutrition, for example, and this can occur between both closely and distantly related species. Studies examining competitive interactions between non‐native species and distantly related native taxa are relatively rare, largely because it is difficult to compare their diets using traditional methods. However, dietary DNA metabarcoding overcomes these limitations by enabling the construction of highly detailed food webs. Here, we use dietary DNA metabarcoding between two generalist native consumers—a reptile (Telfair's skink) and a Scolopendra centipede (Serpent Island centipede)—and the hyperabundant non‐native ant community to test which consumer groups prey upon one another and partition food resources. To determine how non‐native ants fit into a native community, we calculated dietary composition, niche overlap, and dietary diversity of ants, centipedes, and skinks on Round Island, a small 2.19‐km 2 oceanic island located 22.5 km north‐east of Mauritius. We observed distinct partitioning of food resources among the three consumer groups—skinks, centipedes, and ants—and found that the level of predation between these groups varied. Skinks and centipedes frequently consumed non‐native ants, which may represent an important nutritional resource for both native consumers. Dietary differences persisted through seasons despite large shifts in the availability of food and concomitant diet composition for all three consumers. We conclude that non‐native ants fit into the biological community of Round Island as both prey for native consumers and extreme omnivorous generalists, but not necessarily at the expense of the native consumers because it is unlikely the consumers are competing for food resources. Our results suggest that abundant non‐native generalists, which are highly invasive in much of their introduced range, can infiltrate native food webs without exerting strong competitive forces on other common native generalist species.